DEVELOPMENT OF AN INTERACTIVE DIGITAL STORYBOOK BASED ON LOCAL WISDOM TO ENHANCE ELEMENTARY SCHOOL STUDENTS’ READING LITERACY - Dwi Anissa Setya Pratiwi; Moch Bayu Ibrahim; Trio Erawati Siregar (Universitas Majalengka, 2026)
This study aims to develop, evaluate the feasibility, and analyze the effectiveness of a local wisdom-based interactive digital storybook in improving elementary school students’ reading literacy. This research is motivated by the low level of students’ reading literacy and the limited use of innovative and contextual instructional media. The study employed a Research and Development (R&D) approach using the 4D model, which consists of define, design, develop, and disseminate stages. The participants were 25 third-grade students of MI Ar-Rahman Rawa Kalong, Bogor Regency. Data collection techniques included expert validation questionnaires (material, media, and language), student response questionnaires, pretest and posttest, and observations. The data were analyzed using descriptive quantitative and inferential statistics through percentage calculation, N-Gain, and paired sample t-test. The results show that the developed product is a local wisdom-based interactive digital storybook in flipbook format, equipped with audio, animations, and interactive quizzes. Expert validation results indicate that the media is categorized as very feasible, with an average percentage of 89.96%. In addition, student responses demonstrate a very high level of practicality, with a percentage of 90.8%. The effectiveness test results reveal a significant improvement in students’ reading literacy, as indicated by an average N-Gain score of 0.64 (moderate category) and statistically significant t-test results (p < 0.05). In conclusion, the local wisdom-based interactive digital storybook is proven to be valid, practical, and effective in improving students’ reading literacy, and it has strong potential as an innovative instructional medium that aligns with the needs of 21st-century learning in elementary education.